2019
DOI: 10.1016/j.taap.2018.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cytotoxicity of respirable surface-treated/untreated calcium carbonate rock dust particles in vitro

Abstract: Calcium carbonate rock dust (RD) is used in mining to reduce the explosivity of aerosolized coal. During the dusting procedures, potential for human exposure occurs, raising health concerns. To improve RD aerosolization, several types of anti-caking surface treatments exist. The aim of the study was to evaluate cytotoxicity of four respirable RD samples: untreated/treated limestone (UL/TL), untreated/treated marble (UM/TM), and crystalline silica (SiO2) as a positive control in A549 and THP-1 transformed human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…In addition, further work is required to confirm that the association is causal and identify the molecular processes driving the cellular response with a view to identifying potential therapeutic approaches. While the exposure protocol we used is well justified on the basis of previous work, 7,16,26 a time course and dose–response study is needed to investigate whether the association between chemical characteristic of particle and cellular response remains consistent under a range of conditions. Nonetheless, our study used a systematic approach to identify associations between the chemistry of coal particles and the response in a range of lung cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, further work is required to confirm that the association is causal and identify the molecular processes driving the cellular response with a view to identifying potential therapeutic approaches. While the exposure protocol we used is well justified on the basis of previous work, 7,16,26 a time course and dose–response study is needed to investigate whether the association between chemical characteristic of particle and cellular response remains consistent under a range of conditions. Nonetheless, our study used a systematic approach to identify associations between the chemistry of coal particles and the response in a range of lung cell types.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by epidemiological studies showing correlations between coal seam geochemistry and the prevalence of CWP 12 and early in vitro studies showing that cell growth is inhibited to a greater extent by leachates of coal collected from areas with a higher incidence of CWP 8 . Recent in vitro studies have focused on exploring non‐carbon components of coal mine dust as the key reactive compounds leading to coal‐induced lung injury 7,12–16 . However, data from these studies are contradictory, highlighting the necessity for new studies that consider all components of coal mine dusts and how these impact responses in a range of cell types.…”
Section: Introductionmentioning
confidence: 99%
“…NRCWE-013, NRCWE-014, and NRCWE-015 were apparently also associated with a silica contamination indicated by the relatively large amounts of TMOS in the PLE extracts. Calcium carbonate particles are often surface treated with stearic acid [67] which may also change the toxicity [68].…”
Section: Resultsmentioning
confidence: 99%
“…While acute exposure to calcite dust has not been shown to induce significant cytotoxicity, respiratory irritation is possible, which might contribute to a higher risk of chronic obstructive pulmonary disease (COPD) [7][8][9]. That said, whenever health effects due to RD products have been reported, the respirable crystalline silica (RCS) content was proposed to be the most likely cause [9].…”
Section: Introductionmentioning
confidence: 99%
“…While acute exposure to calcite dust has not been shown to induce significant cytotoxicity, respiratory irritation is possible, which might contribute to a higher risk of chronic obstructive pulmonary disease (COPD) [7][8][9]. That said, whenever health effects due to RD products have been reported, the respirable crystalline silica (RCS) content was proposed to be the most likely cause [9]. It is noted that United States regulation does allow for a small percentage of respirable crystalline silica (RCS) in RD products (≤4% by mass, per 30CFR §75.2), but studies have consistently indicated that common products typically do not exceed the standard [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%